A Critical Network Governance Issues in Social Sciences Discipline: A Literature Review - Tukijan, Tukijan; Rahmat, Al Fauzi; Muksin, Dafrin; Pora, Sahrul; Putra, Muhammad Ade (Jurnal Ilmiah Peuradeun, 2024)
Some scholars have underlined network governance issues in theoretical, conceptual, operational, and practical terms. However, it is still requested to core map this issue, as past scholars have lacked attention. Therefore, this paper explores network governance’s pivotal issues and proposes a theoretical model. A systematic literature review was conducted using Scopus database sources, and NVivo 12 Plus software was used as an assistive qualitative data analysis tool. This study revealed several viewpoints. First, network governance has received much attention over the last decade. Second, some essential core key terms are linked to network governance issues, such as social, public, government, policy, actor, political, institutional, and organizational. In addition, we proposed a theoretical model that can be used as a recommendation for future studies.